(untitled) (Journal of educational development exploration, 2026)
In the digital and intelligent era, the classroom teaching of theoretical courses in new liberal arts urgently requires reform in multiple aspects, including teaching obje- ctives, teaching content, teaching methods, teaching means, and evaluation methods. Scenario-based teaching, as a comprehensive teaching method, integrates digital technology, scenario ecology, role immersion, and task-driven learning, providing a new teaching paradigm for theoretical courses in new liberal arts.The five-element model of scenario-based teaching includes: teaching scenarios, teaching facilities, learning roles, learning activities, and values-shaping.The scenario-based teaching of new liberal arts theoretical courses should adhere to the principles of overall planning and role-activity correspondence. It can be achieved through various paths, including the digital and intelligent reconstruction of teaching objectives, problem chain-driven teaching content, enhanced feedback interaction through teaching facilities, immersive role engagement for teaching roles, and scenario-based infiltration of classroom values.